Trade costs and agricultural trade in Central Asia; Handelskosten und Agrarhandel in Zentralasien - Richard Pomfret (Leibniz Institute of Agricultural Development in Transition Economies (IAMO), 2014)
Central Asian governments frequently express the goal of economic diversification, and specifically of diversifying their agricultural sector, but with little actual impact. Diversification has not happened because high trade costs discourage farmers, potential foreign investors and others from identifying new products that could be produced competitively. This paper reviews recent international literature on trade costs, and the limited Central Asian evidence. Because of high trade costs, the phenomenon of global value chains has scarcely touched Central Asia, apart from a few cases in the Kyrgyz Republic. The examples of clothing and beans illustrate how a Central Asian country has joined international value chains. The paper draws conclusions about how Central Asian countries wishing to diversify their agricultural sectors could draw upon this experience. – – Viele zentralasiatische Regierungen verfolgen das Ziel der wirtschaftlichen Diversifizierung, insbesondere im Agrarsektor, allerdings oftmals mit geringer Wirkung. Hohe Handelskosten halten Landwirte, potenzielle ausländische Investoren und andere Akteure davon ab, neue Produkte zu entwickeln, die sie anschließend wettbewerbsfähig vermarkten können. Auf diese Weise wird eine wirtschaftliche Diversifizierung verhindert. Dieser Beitrag behandelt einige neuere internationale Arbeiten über Handelskosten und stellt empirisches Material mit Zentralasienbezug vor. Aufgrund der hohen Handelskosten hat Zentralasien, abgesehen von einigen Fällen in Kirgisistan, bisher kaum teil an globalen Wertschöpfungsketten. Beispiele aus den Bereichen Kleidung und Bohnenproduktion zeigen, wie ein zentralasiatisches Land in internationale Wertschöpfungsketten eingegliedert werden kann. Abschließend wird aufgezeigt, wie zentralasiatische Länder von diesen Erfahrungen lernen können, wenn sie eine weitere Diversifizierung ihrer Wirtschaft anstreben.
urn:nbn:de:gbv:3:2-28684
Keywords: F13; F14; Q17; 330; trade costs; agricultural trade; Central Asia; Handelskosten; Agrarhandel; Zentralasien